Evaluation of experimental techniques for performance estimation of post-tensioned concrete beams - Castellanos-Toro, Sebastián; Panesso, Angélica M.; Marulanda, Johannio; Ortiz, Albert R.; Cruz, Alejandro; Thomson, Peter (Construction & building materials, 2023)
•Cyclic load test (CLT) was applied on PC beams to control the level of deterioration.•Assessed PC beam performance estimation techniques with experimental data only.•Static, vibration and acoustic emission results were related via a coefficient of determination.•The effectiveness of the evaluated techniques is related to their capabilities and limitations. Structural health monitoring (SHM) techniques have become a significant subject in structural evaluation due to the development of non-destructive methods used to monitor and assess the integrity of structures. This paper aims to investigate the effect of damage on the flexural performance indicators and dynamic characteristics of post-tensioned concrete (PC) beams, using both static and vibration tests. The beams were tested at several load levels to reproduce different load stages of a PC member: pre-cracking, during and after the formation of initial cracks, and finally, during and after the formation of larger significant cracks. The performance of the elements is evaluated based on static data, energy calculations, and the three criteria of ACI 437 recommendations. Data from the vibration tests were used to identify the changes in modal parameters after different load levels. Acoustic emission data analysis and results were used to classify the level of damage. Experimental bending stiffness and crack length determination via visual inspection was used as control parameters to assess the deterioration levels of the beams. The outcomes of this study show the relationship level among the different experimental responses obtained: flexural performances, the presence of damage in the beams, and natural frequencies. By considering the relationships of the SHM techniques and their individual findings, the evaluation of performance indicators or damage classification in rectangular concrete prestressed beams reveals that the main limitation is the required knowledge about the previous response of the system.